Profile of Serum Interleukin-31 Levels in Atopic Dermatitis - Dewi Kusumawati; Cita Rosita Prakoeswa; Rahmadewi Rahmadewi (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: Atopic dermatitis (AD) is a chronic inflammatory skin disorder characterized by pruritic skin lesion. Pathogenesis of AD is not fully understood, but recent studies demonstrate the role of interleukin-31 (IL-31). This cytokine is considered to be a potential mediator inducing pruritus in AD. Several studies reported a direct correlation between serum IL-31 level and severity of AD, probably due to the ability of this cytokine to increase the inflammatory response through the initiation of the expression of proinflammatory cytokines and chemokines. Purpose: To evaluate the serum level of IL-31 in AD patients. Methods: Thirty-four AD patients who defined according to the criteria of United Kingdom (UK) Working Party were included in this descriptive observational cross-sectional study. Samples were taken from peripheral venous blood and IL-31 serum levels were measured using ELISA. Results: Mean IL-31 serum level was 99.43±72.91 pg/mL, with the lowest level of 6.84 pg/mL and the highest level of 281.25 pg/mL. Conclusion: IL-31 seems to have a role in atopic dermatitis but further investigation is required.